Phosphatidylcholine suppresses inflammatory responses in LPS-stimulated MG6 microglial cells by inhibiting NF-κB/JNK/p38 MAPK signaling - Sachiko Mizuno; Yuki Kurobe-Takashima; Daisuke Kuriki; Kenta Susaki; Kurataka Otsuka; Tomoko Tsuchihashi; Keiko Abe; Shoko Kobayashi (PLoS ONE, 2025)
Phosphatidylcholine (PC), a choline-containing phospholipid abundant in chicken eggs, is widely consumed as a dietary supplement. Epidemiological studies suggest that PC intake may improve cognitive function in patients with neurodegenerative diseases such as Alzheimer’s disease, although the underlying mechanisms remain largely unclear. In this study, we investigated the anti-inflammatory effects of PC and its molecular mechanisms using an in vitro inflammation model involving lipopolysaccharide (LPS)-stimulated MG6 mouse microglial cells. PC significantly suppressed the LPS-induced expression of pro-inflammatory cytokines, including tumor necrosis factor-α (TNF-α), interleukin-1β (IL-1β), and interleukin-6 (IL-6). Mechanistically, PC inhibited the phosphorylation of inhibitor kappa Bα (IκBα), thereby preventing the nuclear translocation of nuclear factor-κB (NF-κB). PC also reduced the phosphorylation of c-Jun N-terminal kinase (JNK) and p38 mitogen-activated protein kinase (MAPK), and suppressed the nuclear translocation of activator protein-1 (AP-1), composed of c-Fos and c-Jun. These findings indicate that PC attenuates LPS-induced microglial inflammation via the NF-κB and JNK/p38 MAPK signaling pathways. Given the proposed role of chronic neuroinflammation in the progression of neurodegenerative diseases, the anti-inflammatory properties of PC demonstrated here may provide new insights into its potential contribution to maintaining brain health.